Assessment Of Skills Needed Of A Craftsman In Servicing, Maintaining And Repairing Of Mechanical Plants In Building Industry In Rivers State. - Deebom, MtormaBari TamBari; Dokubo, Isaac Nwojiewho (Advances in Social Sciences Research Journal, 2018)
This study examines the assessment of skills needed of a craftsman in servicing, maintaining and repairing of mechanical plants in building industry in Rivers State. One research question guided the study while two hypotheses were formulated and tested at 0.05 level of significance. Descriptive survey research design was used and the population of the study was 172 respondents from technical colleges in Rivers State. A sample of 172 respondents (29 teachers and 143 students) was used for the study. The data for analysis was collected through a self-constructed instrument titled “Assessment of Skills Needed by Mechanical Craftsman Questionnaire” (ASNMCQ) which was properly validated. A reliability coefficient was established for the instrument through Cronbach Alpha method whose coefficient was 0.84. The research questions were analysed using descriptive statistics of mean with standard deviation while hypotheses were tested with z-test. The study revealed that testing the properties of metals, marking out, metal heat treatment, drilling operations and metal scrapping and lapping are operational skills needed by craftsman for the servicing, maintaining and repairing of plants. It was recommended amongst others that NABTEB and similar examination bodies could consider using assessing students’ practical skills at NTC level as a criterion for awarding of certificate to mechanical engineering trades students.